Uso do balanço hídrico climatológico para subsidiar tomadas de decisão quanto ao manejo de bacias hidrográficas - Carvalho Neto, Romário Moraes (2011)
The human being has always been and always will be dependent on water, like all forms of life on the planet earth. Considering this, hydrology becomes fundamental to all plans, either on urban or rural areas. Therefore it is necessary several studies on the various factors related to the hydrological cycle and its positions on time and space in order to plan for the various situations. Knowing the relationship between soil and environment is important to manage and preserve this natural resource and the various aspects related to it. This work aims to migrate the scale from 1:750.000 of the Soil Map to the Cachoeira Cinco Veados Watershed, Rio Grande do Sul State, Brazil, through field observations as toposequence, landscape and soil cuts exposed on the road sides of the basin, creating a soil map for the basin, regionalizing and discriminating the different soils mapped to the level of Order (first Category Level). The work also aims to analyze this basin s soil map and classify it according to the different land uses in order to represent the Soil Available Water Capacity (CAD) and calculate the climatic water balance of the watershed. To do it so, the average temperatures throughout the year were analyzed to estimate the potential evapotranspiration by the Thornthwaite method as well as the rainfall of the basin throughout the year. The spreadsheet BHídrico V.3.2 was used to calculate the basin s water balance through the climatological balance method of Thornthwaite & Mather. All the months showed to have water availability for the Cachoeira Cinco Veados watershed, with the exception of December. The conclusion is that throughout the whole hydrological year, the potential evapotranspiration does not exceed the minimum rainfall of the watershed and there are the necessary conditions for the development of plants, with the exception of December only. For this reason, a more specific analysis was directed to the climatic water balance of this month. The resulting map of the climatic water balance for the month of December was analyzed within each one of the four Thiessen polygons created for this purpose. The use of the climatological water balance is efficient on the orientation for making decisions on watershed managing.